Preservation of dog semen in three extenders at refrigeration temperature - Kadirvel G (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1998)
With the ultimate objective of evolving a suitable diluent for preservation of dog semen at 4°C, semen was collected from six mongrel dogs maintained in kennels at Veterinary college hospital, Mannuthy. A total of 36 ejaculates, six from each dog was collected by digital manipulation and physical and morphological characters were evaluated. Three extenders viz., Egg Yolk Tris (TYT), Egg Yolk citrate glycine glucose (EYCGG) and Goat milk (GM) were used for preservation of semen. Sperm motility, percentage of live sperm, abnormal spermatozoa and acrosomal integrity were evaluated at 24 hours interval for five days after preservation at 4°C in the above extenders. Six out of seven dogs showed good response to digital manipulation and ejaculated good quality semen without teaser bitch. The overall mean volume of first, second and third fraction of semen was 0.63 ± 0.07 ml, 1.29 ± 0.08 ml and 4.12 ± 0.23 ml respectively. The colour and consistency of the first and third fraction was clear, watery and second fraction was thickmilkly to thin milkly. The average mass activity of sperm rich fraction of semen was ++(+) and the density was DD. The mean initial sperm motility was 86.67 ± 1.07 per cent.